LINGUISTIC TRAILS THROUGH THE FOREST: TRACKING DEIXIS IN MAVKA: THE FOREST SONG - Rositasari, Tri; Sulaiman, Masagus; Andrini, Andrini (Universitas Muhammadiyah Palembang, 2025)
This research aimed to find out the kinds and meanings of deixis, as well as its potential recommendation to teaching English as a foreign language (TEFL). This research employed a qualitative research method case study design to understand the phenomenon that the research subject experienced, such as behaviour, perception, motivation, action, and so forth, was the goal of qualitative research (Moleong, 2017). In this research, the researchers used two kinds of data sources. The primary data and secondary data. The primary data was movie script of Mavka: The forest song movie by Malamuzh and Oleksandra Ruban and secondary data was journals that related to deixis. To collect the data, the researchers applied triangulation in term of documentation technique. To analyse the data, the researchers applied triangulation. This study identified 23 instances of person deixis which include first-person, second-person, and third-person references. The researchers also found out 10 places deixis, 12 times deixis, 5 discourses deixis, and 6 social deixis.